Analysis of the Imbalance of Regional Income Components in Binjai City Using the Regional Financial Ratio Approach - Sri Risqi Widiyanti; Vina Arnita; An Suci Azzahra (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2026)
Regional revenue is a fundamental financial resource reflecting fiscal capacity and supporting the implementation of regional autonomy and sustainable development. The composition and balance of regional revenue components—local own-source revenue, transfer revenue, and other legitimate regional revenues—determine a region’s level of fiscal independence. In practice, many local governments experience structural revenue imbalances due to high dependence on central government transfers. This study examines the development and degree of imbalance among regional revenue components in Binjai City during the 2020–2024 period. The research adopts a descriptive quantitative approach using secondary data from budget realization reports obtained through the Regional Budget Data Portal of the Directorate General of Fiscal Balance. Data are analyzed using growth ratios and contribution ratios to assess revenue dynamics, fiscal dependence, and revenue structure. The findings reveal that local own-source revenue shows fluctuating growth and contributes relatively little to total regional revenue. Transfer revenue consistently dominates the revenue structure, while other legitimate regional revenues exhibit high volatility and a declining contribution trend. These results indicate that Binjai City’s fiscal independence remains low and that imbalances in regional revenue composition persist.